Islamic Microfinance as a Tool for Financial Inclusion: A Comparative Analysis with Conventional Microfinance - Mehwish Malik (Journal of Accounting and Finance in Emerging Economies)
Purpose: Microfinance has played a substantial role in providing financial facilities to marginalized populations, particularly in emerging countries, by offering credit, savings, and insurance to individuals who don’t have access to traditional banking services. This study compares the effectiveness of conventional and Islamic microfinance in poverty reduction, with a emphasis on Pakistan’s microfinance sector.